2013
DOI: 10.1007/s13201-012-0073-y
|View full text |Cite
|
Sign up to set email alerts
|

Batch sorption dynamics, kinetics and equilibrium studies of Cr(VI), Ni(II) and Cu(II) from aqueous phase using agricultural residues

Abstract: In the present study, the agricultural residues viz., Syzygium cumini and Populus deltoides leaves powder have been used for the biosorption of Cu(II), Ni(II), and Cr(VI) from aqueous solutions. FTIR and SEM analysis of the biosorbents were performed to explore the type of functional groups available for metal binding and to study the surface morphology. Various physico-chemical parameters such as pH, adsorbent dosage, initial metal ion concentration, and equilibrium contact time were studied. Thermodynamic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…An overall 31.49 % reduction in the adsorption capability of MLP was observed at 5th cycle. The decreased adsorption and desorption during the repeated cycles attributed due to structural changes on the surface of sorbent and some of metal ions being held in the intrapores of MLP (Kaur et al 2013). Kaur et al (2013) observed that complete desorption of metal ions from the surface of agricultural residues is not possible even at high acid concentrations.…”
Section: Desorption and Regeneration Studiesmentioning
confidence: 94%
“…An overall 31.49 % reduction in the adsorption capability of MLP was observed at 5th cycle. The decreased adsorption and desorption during the repeated cycles attributed due to structural changes on the surface of sorbent and some of metal ions being held in the intrapores of MLP (Kaur et al 2013). Kaur et al (2013) observed that complete desorption of metal ions from the surface of agricultural residues is not possible even at high acid concentrations.…”
Section: Desorption and Regeneration Studiesmentioning
confidence: 94%
“…Cr (VI) ions are frequently found in chromates (CrO (Gupta et al, 2013). At low pH, the concentration of Cr 2 O 2− 7 increases whereas, at higher pH (6.0), Cr (VI) is present in solution in the (Kaur, Singh, Khare, Cameotra, & Ali, 2013). Desorption efficiency for both the biosorbents was further evaluated from the quantitative amount of metal ions desorbed to the metal ions adsorbed in the desorption medium, as per the expression (2) (Yoonaiwong, Kaewsarn, & Reanprayoon, 2011): …”
Section: Effect Of Different Parameters On Biosoption Capabilitymentioning
confidence: 99%
“…This is due to, at lower concentrations, the ratio of active adsorption sites to the initial metal ions is larger, resulting in higher removal efficiency (Ding et al 2012). However, with increasing metal ion concentration, the functional groups on biomass surface could be saturated, and there were a few available active sites on the biomass surface (Kaur et al 2013). As a result, at higher metal concentrations, the metal ions would compete for the available binding sites.…”
Section: Biosorbent Characterizationmentioning
confidence: 99%
“…Biosorption is a process that utilizes inexpensive biomass to sequester toxic heavy metals from water (Mishra 2014). The biosorbent term refers to material derived from microbial biomass, seaweed or plants that exhibit adsorptive property, so that materials of natural origin (such as agricultural wastes) are generally used in biosorption studies (Kaur et al 2013). Particularly, biosorption is convenient for the elimination of contaminants from industrial effluents.…”
Section: Introductionmentioning
confidence: 99%